NOS3 rs3918188C>A is associated with susceptibility to resistant hypertension while CES1 genetic variation was not associated with resistant hypertension among South Africans - Katsukunya, Jonathan N.; Naicker, Revina; Soko, Nyarai D.; Blom, Dirk; Sinxadi, Phumla; Chimusa, Emile R.; Rayner, Brian; Jones, Erika; Dandara, Collet (Frontiers in Genetics, 2025)
IntroductionGenetic variation in genes coding for enzymes metabolising antihypertensive drugs, may affect the efficacy of angiotensin converting enzyme (ACE) inhibitors such as enalapril, potentially leading to resistant hypertension (RHTN). We set out to evaluate the contribution of genetic variation in CES1 and NOS3 genes on susceptibility to RHTN, as well as estimate the frequencies of CES1 copy number variation (CNV) in African and Mixed Ancestry (MA) populations of South Africa.MethodsUsing a retrospective age, sex and ethnicity matched case-control study design, 379 participants with hypertension belonging to the African and MA ethnic groups were recruited. Cases were participants with RHTN (i.e., blood pressure (BP) ≥140/90 mmHg on ≥3 antihypertensive drugs or BP < 140/90 mmHg on >3 antihypertensive drugs, including a diuretic). Cases were matched to controls with similar characteristics (age (±5 years), sex and ethnicity) in a 1:1 ratio. Controls were participants with hypertension that was under control (BP < 140/90 mmHg on ≤3 antihypertensive drugs). Five polymorphisms in CES1 and NOS3 were characterized using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), quantitative PCR and validated using Sanger sequencing. The additive model of inheritance and multivariable logistic regression were used to determine associations between genotypes and RHTN while adjusting for potential confounding variables.Results and discussionNOS3 rs3918188A/A (aOR: 0.13; CI: 0.04–0.41; P = 0.0009) genotype and NOS3 rs2070744–rs1798883–rs3918188G–T–A haplotype (OR: 0.54; CI: 0.37–0.78; P = 0.001) appeared to confer protection against RHTN among MA participants only. CES1 rs2244613C>A and CES1 CNV were not significantly associated with RHTN. However, there appeared to be quantitative differences in CES1 CNV profiles across ethnic groups. We speculate that NOS3 rs3918188A allele may affect NOS3 gene expression, potentially leading to increased amounts of the vasodilator, nitric oxide (NO) and favourable outcomes in individuals taking antihypertensives drugs such as enalapril.ConclusionNOS3 genetic variation seems important in the susceptibility to RHTN among Africans and requires further studies.